(untitled) (Revista Contexto & Saúde, 2024)
The study aimed to investigate the requirements for building an application for safe discharge and care transition for newborns. This is an exploratory study, carried out with 12 nursing professionals who work in newborn care in Brazil’s northeast. Data was collected using a form between May and September 2023. Meleis’ Care Transition theoretical framework was adopted. Three units of meaning emerged: Concept of safe hospital discharge and the transition of newborn care; Readiness for safe newborn discharge; and Expectations about the construction and use of care technology for the safe discharge of newborns. The requirements involved the need to unveil the main criteria and parameters involved in discharge, as well as the ability to connect health professionals to family members/caregivers of the newborn, with the ability to instruct and clarify doubts, highlighting the importance of the participation of the multidisciplinary team in the development, as well as in the dissemination of the application. Therefore, the requirements for care technology were identified and will subsidize the creation of an application to support the discharge of newborn patients, with the aim of improving the care transition and safety in this population’s discharge.